Sucession Planning In Family Business: A Take A Look At A Tourism Business - Billy Arlando Sutandyo; Maria Yosephine Dwi Hayu Agustini (Journal of Management and Business Environment (JMBE), 2021)
Family business is a dominant type of business in Indonesia. However, studies have confirmed that only few of them can sustain longer. Succession has not been in the agenda of most family businesses in Indonesia. This research aims at observing succession process in a family business in order to understand how the process is conducted and how well it is according to Walsh’s. The researched family business is a business operating in tourism sector, which is processing succession to the second generation. The research gathered information from the owner and the two children who are the successors. Interview and observation were to gather information and descriptive analytic was applied to describe the process of succession. The results indicate that the succession planning in terms of management succession and ownership succession run relatively well and the desired outcomes can be identified clearly. However, the successors are considered as not yet ready for taking the business. Involving them in the strategic activities can possibly fasten the process to make them being ready.